2019
DOI: 10.1021/acs.jpclett.9b02678
|View full text |Cite
|
Sign up to set email alerts
|

Broad-Band Dielectric Spectroscopy Reveals Peak Values of Conductivity and Permittivity Switching upon Spin Crossover

Abstract: We use broad-band dielectric spectroscopy to investigate the spin-state dependence of electrical properties of the [Fe(Htrz) 2 (trz)](BF 4 ) spin crossover complex. We show that the Havriliak−Negami theory can fully describe the variation of the complex dielectric permittivity of the material across the pressure−temperature phase diagram. The analysis reveals three dielectric relaxation processes, which we attribute to electrode/interface polarization, dipole relaxation, and charge transport relaxation. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…254 Bousseksou, Salmon and co-workers performed most of the work with this material (Figure 13). [255][256][257][258][259][260] These different studies were performed with different set-ups (two probe contacts or interdigitated electrodes, 259,260 DC 258 or AC conductivities 255,261,257 ) and using samples with slightly different crystallite sizes (0.7-5 µm x 200-300 nm high aspect ratio needles [258][259][260] or ~200 nm nearly spherical particles 255,261,257,258 ) and large electrode gaps of several micrometres. Nonetheless, most of them yielded comparable results and pointed to the same conclusion: the HS form is less conductive than the LS state (Figure 13b).…”
Section: Electrical Conductivity and Scomentioning
confidence: 99%
See 1 more Smart Citation
“…254 Bousseksou, Salmon and co-workers performed most of the work with this material (Figure 13). [255][256][257][258][259][260] These different studies were performed with different set-ups (two probe contacts or interdigitated electrodes, 259,260 DC 258 or AC conductivities 255,261,257 ) and using samples with slightly different crystallite sizes (0.7-5 µm x 200-300 nm high aspect ratio needles [258][259][260] or ~200 nm nearly spherical particles 255,261,257,258 ) and large electrode gaps of several micrometres. Nonetheless, most of them yielded comparable results and pointed to the same conclusion: the HS form is less conductive than the LS state (Figure 13b).…”
Section: Electrical Conductivity and Scomentioning
confidence: 99%
“…Hence, they associate the higher conductivity in the LS state to its higher stiffness (i.e., higher phonon frequencies), which results in higher hopping rates. 257 However, in a separate study, Dugay, Coronado and co-workers used time-resolved microwave conductivity to show that there is actually two different transport regimes in the LS state: tunnelling through shallow traps which transits into a trap free hopping regime with increasing temperature. 264 All the above studies of [Fe(Htrz)2(trz)](BF4) show an opposite trend to the results reported by Prins et al, which showed that the HS state has a larger conductivity than its counterpart.…”
Section: Electrical Conductivity and Scomentioning
confidence: 99%
“…In particular, measurements on nanoelectronic devices based on a single SCO nanoparticle showed a more conducting HS state [13]. The reverse situation has been observed in general for particle assemblies [2][3][4][5][6][14][15][16]. This intriguing Magnetochemistry 2020, 6, 31 2 of 8 difference arises most probably due to the different charge transport mechanisms involved in the different experiments (e.g., tunneling vs. hopping).…”
Section: Introductionmentioning
confidence: 96%
“…In the last decade, an important number of papers focused on the charge transport properties of spin crossover (SCO) materials at different scales: bulk [2][3][4][5][6][7], single molecule [8][9][10][11][12], nano-and micro-particles [13][14][15][16], composites [17], and thin films [18][19][20][21], in relation to interesting perspectives for the application of these compounds in molecular electronics and spintronics. Many of these findings are covered in recent reviews [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, we have shown that both the thermal [11] and pressure-induced [12] spin transitions in the bulk powder of [Fe(Htrz) 2 (trz)](BF 4 ) are accompanied by a substantial variation (up to three orders of magnitude) of the electrical conductivity, the low spin (LS) form being systematically more conducting than the high spin (HS) counterpart. Broadband dielectric spectroscopic investigations [13,14] pointed out a clear link between the spin-state dependence of the dielectric relaxation frequencies and that of the conductivity. We suggested therefore that the the primary origin of the conductivity drop in the HS state is the global downshift of charge hopping (i.e.…”
Section: Introductionmentioning
confidence: 99%